The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5251/abjna.2011.2.5.752.760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ecologies and severity of Striga weed on rice in sub-Saharan Africa

Abstract: Striga spp. is renowned for causing great losses in cereal production in sub-Saharan Africa. Crop competitiveness with parasitic weeds such as Striga is an important criterion for selection in an initiative to produce and release rice cultivars to farmers that are able to give high and stable yields under low-input conditions. The symptoms of Striga infected rice plants are chlorosis, wilting and stunted growth. Rice yield is reported to be reduced by more than 50% in areas that are infested by the weed. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Haussmann et al (2001a) indicated that one major gene and several minor genes appear to be involved in the stimulation of Striga seed germination using sorghum recombinant inbred populations. Although the lines showing low germination-inducing activity have been reported to express good resistance in bioassays, resistance mediated by low strigolactone production has been, however, described to be less reliable when the Striga infestation pressure is high (Atera et al, 2011). In pearl millet, the heredity of host-plant resistance to Striga is not well described.…”
Section: Nature and Genetic Basis Of Resistancementioning
confidence: 94%
See 1 more Smart Citation
“…Haussmann et al (2001a) indicated that one major gene and several minor genes appear to be involved in the stimulation of Striga seed germination using sorghum recombinant inbred populations. Although the lines showing low germination-inducing activity have been reported to express good resistance in bioassays, resistance mediated by low strigolactone production has been, however, described to be less reliable when the Striga infestation pressure is high (Atera et al, 2011). In pearl millet, the heredity of host-plant resistance to Striga is not well described.…”
Section: Nature and Genetic Basis Of Resistancementioning
confidence: 94%
“…In areas of heavy Striga infestation, yield loss may even reach 90 to 100% (total crop failure) in some years (Ramaiah, 1984;Wilson et al, 2000;Gressel et al, 2004). As a result, farmers have been reported to be eventually forced to abandon highly Striga-infested fields (Atera et al, 2011). For these poor farmers, millets are the major staple food providing them with carbohydrates and is the main source of vitamins and minerals including zinc and iron, (Andrews and Kumar, 1992;Rai et al, 2012;Bangoura et al, 2011;Mannuramath et al, 2015;Mishra et al, 2014).…”
Section: Importancementioning
confidence: 99%
“…Approximately 40% of the cereal producing area is infected and 300 million people affected (Ejeta, 2007). The most affected are subsistence farmers losing about 20-80% of their crop yield (Atera et al, 2011). In Malawi, the recorded species are S. asiatica, S. aspera, S. gesneriodes and S. forbesii.…”
Section: Introductionmentioning
confidence: 99%
“…Total crop yield loss occurs under heavy infestation. Other losses as result of Striga depend on land use system, soil fertility, crop species and genotype, and rainfall patterns (Atera et al, 2011). The parasite is difficult to control because it has the capacity to produce large number of tiny dust like seeds which can survive in the soil for more than 10 years (Hearne, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…and S. forbesii Benth. (Rodenburg et al, 2010;Atera et al, 2011). Among these species S. hermonthica is the most destructive, leading to severe yield losses of over 50% thereby affecting livelihoods of millions of farmers (Franke et al, 2006).…”
Section: Introductionmentioning
confidence: 99%